Multielemental Profile of Peritoneal Fluid in Gynaecology Patients Presenting with Uterine Myomas - Andrea López-Botella; María José Gómez-Torres; José-Luis Todolí-Torró; Raquel Sánchez; Irene Velasco; Maribel Acién (Proceedings)
Introduction: Uterine myomas are benign tumours that usually grow in the uterus [...]